Sakacin Q produced by Lactobacillus curvatus ACU-1: Functionality characterization and antilisterial activity on cooked meat surface - Rivas, Franco Paolo (2014)
This work was conducted to evaluate the antilisterial activity of sakacin Q produced by Lactobacillus curvatus ACU-1 on the surface of cooked pork meat. A genetic re-characterization of the producer strain and a study of the structural genes involved in bacteriocin production were carried out as complementary data. Studies indicated that the bacteriocin was not attached to the producer cells favoring pre-purifications steps. Bacteriocin effectiveness was not compromised by adsorption to meat and fat tissues. Several ways of dispensing the bacteriocin onto the meat surface, namely cell culture, cell free supernatant (CFS), a mixture of both and freeze-dried reconstituted CFS, were investigated. The use of the latter was the most effective one to control Listeria growth within studied systems. L. curvatus ACU-1 and its bacteriocin presented promising technological characteristics that made them suitable for meat biopreservation.